Análise dos efeitos do investimento nacional e do IDE no crescimento económico português de 1997 a 2009 - Silva, Sérgio Oliveira (2013)
Portugal along with the rest of the world, especially when compared with smaller economies, presents a not very favorable economic reality. To better understand the current situation in which Portugal is, we will examine the relationship between domestic investment, foreign direct investment and economic growth of the Portuguese economy between 1997 and 2009. This study begins with a brief review of related literary, then it is analysed graphically the three individual series: gross domestic product (GDP), domestic investment (DI) and foreign direct investment (FDI). Statistically, it is studied the volatility, covariance and correlation of the series under analised. Econometrically, to test the existence of unit root, we used the following tests: Augmented Dickey-Fuller (ADF), Philips Perron (PP), Elliot Rothenberg Stock (ERS) and Kwiatkowski Phillips Schmidt Shin (KPSS). The results did not reject the existence of unit root in each series. Analyzing the cointegration relationship between GDP and the DI, as well as between GDP and FDI using the Johansen test, we conclude the existence of a cointegration relation beytween GDP and DI as well as GDP and FDI. The fact that the series are cointegrated allows us to proceed to the estimation of long-term relationships. To choose the optimal lag for the VAR model, it was used the criteria of Schwarz (SC), Akaike (AIC) and Hannan-Quinn (HQ). In the test for Granger Causality (GC), it was found that GDP influences both the DI and in the FDI, and that the DI granger causes the FDI. The results show that there is single-directional causality between domestic investment and economic growth, there is also single-directional causality from FDI to domestic investment and to economic growth. Rather than crowding out domestic investment, FDI is found to be complementary with domestic investment. Thus, FDI has not only assisted in overcoming shortage of capital, it has also stimulated economic growth through complementing domestic investment in Portugal. The impulse response functions (IRF) identify the effect of shocks from the innovations inherent in the system, in current and future values of the endogenous variables. From the analysis of IRF, it is concluded that the impact of an exogenous shock in error terms of GDP has a persistence of at least 10 lags in the behavior of the variables. Regarding the behavior of both the DI and FDI, we conclude that there is initially a reaction on the part of the variables to shocks but decline continuously and then reverts back to its original level. By comparing the effects of the domestic investment, and foreign direct investment in the Portuguese economic growth from 1997 to 2009, we may conclude that rather than crowding out domestic investment, FDI is found to be complementary with domestic investment. Thus, FDI has not only assisted in overcoming shortage of capital, it has also stimulated economic growth through complementing domestic investment in Portugal.